CFD Simulation on Supercritical Fluid Extraction of Black Pepper's Bioactive Compounds: Single Particle Study - Then , Siew Ping; Panau , Freddie; Samyudia, Yudi (Taylor's University, 2014)
To gain a better understanding on the application of computational fluid dynamics (CFD) towards extraction using supercritical fluid, a single particle study was carried out. The flow behaviour of an ambient supercritical carbon dioxide flowing through a heated black pepper particle in vertical direction was studied. The transfer of heat from the heated particle to supercritical fluid was examined. Various groups of parameters in the following ranges were carried out for the simulations: pressure 3000 psi, 4000 psi and 5000 psi; temperature 4°C, 50°C and 55°C; and solvent flow rate 5 ml min–1, 7.5 ml min–1 and 10 ml min–1. The contour of velocity magnitude and streamline of the flow along the particle were presented. Temperature profile and the local heat flux value on the heated particle surface were captured. The drag coefficients and average Nusselt numbers obtained from the simulations had shown a good agreement with the numerical correlations from literature.